2009
DOI: 10.1590/s1413-70542009000300026
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da radiação gama e do armazenamento na qualidade de padúnculos de caju (Anacardium occidentale L.)

Abstract: RESUMODevido a altas perdas de pedúnculos de caju, métodos de conservação são necessários para um maior aproveitamento dos mesmos. Com esse objetivo, pedúnculos de caju vermelho, maduros, obtidos de cajueiro anão precoce, foram irradiados com doses de 0, 0,5 e 1,0 kGy e armazenados por 9 dias, refrigerados 4 ºC para verificação da estabilidade da qualidade durante o período de armazenamento. Para isso foram realizadas análises químicas, verificando mudanças nos teores de açúcares redutores, Brix, vitamina C e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Cashew apple subjected to the treatment of calcium, showed an increase in the values of total calcium until 15 days of storage, and decreased slightly until the end of the experiment. The treatment of cashew apple from mature dwarf of cashew tree with gamma radiation with doses of 0, 0.5, and 1.0 kGy followed by a storage for nine days at 4°C showed that the levels of vitamin C decreased during storage and according to the applied doses of radiation, while the firmness of the fruits was influenced by both the radiation doses and storage time, increasing during storage and decreasing as the radiation doses increased (Souza et al, 2009).…”
Section: Effects Of Postharvest Process On Physico-chemical Charactermentioning
confidence: 99%
See 1 more Smart Citation
“…Cashew apple subjected to the treatment of calcium, showed an increase in the values of total calcium until 15 days of storage, and decreased slightly until the end of the experiment. The treatment of cashew apple from mature dwarf of cashew tree with gamma radiation with doses of 0, 0.5, and 1.0 kGy followed by a storage for nine days at 4°C showed that the levels of vitamin C decreased during storage and according to the applied doses of radiation, while the firmness of the fruits was influenced by both the radiation doses and storage time, increasing during storage and decreasing as the radiation doses increased (Souza et al, 2009).…”
Section: Effects Of Postharvest Process On Physico-chemical Charactermentioning
confidence: 99%
“…Some studies focused on the physico-chemical characteristics of cashew apple (Assuncao and Mercadante, 2003;Lavinas et al, 2006;Brito et al, 2007;Silva et al, 2008;Michodjehoun-Mestres et al, 2009a;Adou et al, 2011aAdou et al, ,b, 2012 and also on the effects of postharvest process on the physico-chemical quality attributes of cashew (Souza et al,1999(Souza et al, , 2009Falade et al, 2003;Figueiredo et al, 2007;Marques et al, 2007;Martins, et al, 2008;Lima et al, 2010); the effects of processing methods, such as clarification by membrane and enzymatic methods or the use of clarifying agents on the nutritional quality of cashew apple juice have also been investigated. Furthermore, the effect of thermal treatment and high hydrostatic pressure on cashew apple juice have been reported by various workers (Campos et al, 2002;Couri et al, 2003;Jayalekshmy and John, 2004;Abreu et al, 2005;Cianci et al, 2005;Castro et al, 2007;Damasceno et al, 2008;Zepka and Mercadante, 2009;Sampaio et al, 2011;Gyedu-Akoto, 2011;Talasila et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In order to extend the postharvest storage period of cashew apples, several technologies have been adopted, such as refrigeration (Moura et al, 2010), gamma radiation (Souza et al, 2009), and postharvest calcium application (Figueiredo et al, 2007). At preharvest, plant growth regulator treatments have been used aiming to delay ripening and preserve postharvest fruit quality, considering that regulators affect plant growth and development, acting as messengers on a broad spectrum of metabolic processes (Marzouk & Kassem, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Desta forma, torna-se fundamental o desenvolvimento de métodos de conservação que prolonguem a vida útil dos pedúnculos, sem que sua estrutura física original e composição química sejam alteradas e, consequentemente, permitam a oferta destes e de seus derivados durante todo o ano. Levando-se em conta essa tendência de novos métodos de conservação, Souza et al (2009) em trabalho realizado com irradiação gama em pedúnculos do cajueiro, encontraram um aumento da firmeza na concentração de 0,5 kGy com o decorrer do tempo de armazenamento, aumentando com isso a vida útil desses pedúnculos.…”
Section: Introductionunclassified